374 VIDEO ESOPHAGOGRAM CORRELATES OF DYSPHAGIA IN PATIENTS WITH NORMAL LOWER ESOPHAGEAL SPHINCTER. (14th September 2020) - Razia, D; Giulini, L; Bremner, R; Mittal, S
Abstract: : Dysphagia is a common foregut symptom. However, there is poor association between non-obstructive dysphagia and esophageal body peristaltic parameters in patients with normal lower esophageal sphincters (LES). The objective of this retrospective study was to study bolus transit patterns noted on barium esophagogram in patients experiencing dysphagia. Methods: After IRB approval, we queried our esophageal database for patients with normal manometric LES. Jackhammer esophagus, esophageal spasm, previous foregut surgery, and unavailable foregut symptom questionnaires were exclusion criteria. Patients were grouped based on reported dysphagia: 0 = None; 1 = Mild; 2 = Moderate; 3 = Severe/very severe. All barium esophagograms were re-evaluated. Bolus esophageal transit time was studied with patients in both upright and prone positions, using live time stamps at bolus entry/exit. "Barium residue" was defined as persistent contrast on the esophageal wall after bolus exit. "Retrograde escape" referred to barium escaping proximally from the bolus into previously cleared esophagus. ANOVA and χ2 were used. Results: In all, 150 patients met inclusion criteria. 76 (50.1%) were women. Mean age and body mass index were 58.4 ± 14.7 years and 22.9 ± 10.4 kg/m2, respectively. The number of patients in each dysphagia group (0, 1, 2, and 3) were 82(54.7%), 29(19.3%), 25(16.7%) and 14(9.3%), respectively. The difference in mean bolus transit time among dysphagia groups was statistically significant in prone-position swallows (39.3 ± 36.7, 75 ± 74.8, 98.8 ± 85 and 69.6 ± 43.7 seconds; p < 0.001) but not in upright-position swallows (14.6 ± 22, 12.4 ± 8.1, 14.3 ± 8.8 and 12.6 ± 8.2 seconds; p = 0.929; Fig. 1). The prevalence of residual contrast and retrograde escape in prone swallows were comparable among patients reporting dysphagia (p = 0.444, p = 0.173). Conclusion: Bolus transit time in prone-position barium swallows is simple to assess, and correlates with dysphagia reported by patients with normal lower esophageal sphincters. However, further studies with comprehensive dysphagia score are needed.